Prevalence of Trypanosomiasis of Wild Rats (Rattus sp.) in Banyuwangi - Zhaza Afililla; Lucia Tri Suwanti; Sri Agus Sudjarwo; Setiawan Koesdarto; Hani Plumeriastuti (Universitas Airlangga, 2017)
The aim of this research was to investigate the number of prevalence of Trypanosomiasis of wild rats in Banyuwangi. Sixty wild rats were trapped from human residence, markets and rice fields in Banyuwangi. Rat`s Â blood smear was stained by Giemsa. The result show that one (1.67%.) of 60 blood sample was appear Trypanosoma sp.. Â The prevalence of Trypanosomiasis of wild rats in Banyuwangi was 1.67%.